If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -5 = -47 + 4x Reorder the terms: -5 + -3x = -47 + 4x Solving -5 + -3x = -47 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + -3x + -4x = -47 + 4x + -4x Combine like terms: -3x + -4x = -7x -5 + -7x = -47 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + -7x = -47 + 0 -5 + -7x = -47 Add '5' to each side of the equation. -5 + 5 + -7x = -47 + 5 Combine like terms: -5 + 5 = 0 0 + -7x = -47 + 5 -7x = -47 + 5 Combine like terms: -47 + 5 = -42 -7x = -42 Divide each side by '-7'. x = 6 Simplifying x = 6
| 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 | | y-5-2=10 | | 12x-13+8=2x | | 4=x+x+2 | | 12x+4-26=-2(3x-82) | | 2y-6x-4=0 | | 10w+5-3w=40 | | 7x-(2x-12)=-8 | | 25x=10-3+5x | | 5(x+2)-(3x-8)= | | 6+(n+4)+(n+4)=51 | | 6+(n+2)+(n+4)=51 | | n+(n+2)+(n+4)=51 | | 8x=240 | | (3x+2)-2(x-4)=7 | | 12n=132 | | -2x+7+x=15 | | 8x=260 | | -11x*-11x+6x-2x*2x+9= | | 8(7-1y)=-24 | | 2y-2=3y | | 2b(a+2)-a(3-b)+2(a+b-1)= | | 5v^2+4=5 | | N+6=-2 |